2022
DOI: 10.1093/mnras/stac3750
|View full text |Cite
|
Sign up to set email alerts
|

Strong toroidal magnetic fields sustained by the elastic crust in a neutron star

Abstract: We investigate new solutions for magnetized neutron stars with a barotropic core in magnetohydrodynamic (MHD) equilibrium and a magneto-elastic crust, which was neglected by previous studies concerning stars in MHD equilibrium. The Lorentz force of the barotropic star is purely irrotational and the structures of magnetic fields are constrained. By contrast, a solenoidal component of the Lorentz force exists in the elastic crust and the structures of the magnetic fields are less restricted. We find that the min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The Lorentz force is comparable in magnitude to the elastic force in the crust. However, only static magneto-elastic equilibria of the crust have been studied thus far (Kojima et al 2021(Kojima et al , 2022Fujisawa et al 2023). These studies demonstrated that neutron-star models with strong magnetic fields are possible owing to the elasticity of the crust.…”
Section: Introductionmentioning
confidence: 99%
“…The Lorentz force is comparable in magnitude to the elastic force in the crust. However, only static magneto-elastic equilibria of the crust have been studied thus far (Kojima et al 2021(Kojima et al , 2022Fujisawa et al 2023). These studies demonstrated that neutron-star models with strong magnetic fields are possible owing to the elasticity of the crust.…”
Section: Introductionmentioning
confidence: 99%
“…The Lorentz force is comparable in magnitude to the elastic force in the crust. However, only static magneto-elastic equilibria of the crust have been studied thus far (Kojima et al 2021(Kojima et al , 2022Fujisawa et al 2023). These studies demonstrated that neutron star models with strong magnetic fields are possible owing to the elasticity of the crust.…”
Section: Introductionmentioning
confidence: 99%